Strategi Guru Menangani Anak Berkebutuhan Khusus (Speech Delay) dalam Pembelajaran Kelas III SDIT Ulil Albab - Dewi Lafayza Khaleda Zia; Nova Estu Harsiwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores learning strategies implemented by educators in handling students with speech delay at the third-grade level of SDIT Ulil Albab. The research urgency stems from the need for personalized and adaptive learning strategies to accommodate the unique characteristics of students with communication challenges. Using a qualitative descriptive approach, the study employs observation, interviews, and document analysis as data collection methods. The findings reveal the effectiveness of several strategies, including systematic instructional communication, learning approach adjustments, and continuous mentoring. The implementation of these strategies not only impacts verbal competency enhancement but also strengthens students' psychosocial aspects within regular learning contexts. Research implications highlight that organized and adaptive learning strategies contribute significantly to creating an inclusive and supportive learning environment for students with speech delay. These findings are projected to serve as constructive references for education practitioners and policymakers in developing more optimal inclusive learning models.